ASSESSNING WRITING SKILLS: TIPS AND SUGGESSIONS - Abdurakhmonova Makhfuza Olimovna (Research Focus International Scientific Journal, 2025)
By evaluating your writing, you are making a commitment to make it better. Making changes to documents and fixing mistakes is surely part of your effort to get better. But evaluating your writing might also spur you on to write more. Your writing will get better with practice. The educational outcomes of students are closely related to evaluating and providing feedback. Giving your students insightful, in-depth comments on their writing is crucial in an online setting so they can see where they are succeeding at expressing their thoughts and where they still have potential for improvement. Responding to students in a remote course in a clear, involved, and targeted way gives you the chance to establish a rapport with them and help them study both within and outside of the course.